Disinflation in a DSGE Perspective: Sacrifice Ratio or Welfare Gain Ratio? - Guido Ascari; Tiziano Ropele (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
When used to examine disinflation monetary policies, the current workhorse dynamic stochastic general equilibrium model of business cycle fluctuations is able to quantitatively account for the main stylized facts in terms of recessionary effects and sacrifice ratio. We complement the transitional analysis of the short-run costs with a rigorous welfare evaluation and show that, despite the long-lasting economic downturn, disinflation entails non-zero overall welfare gains.
Keywords: E31; E5; 330; Disinflation; Sacrifice ratio; Non-linearities